Statistik im DDR-Wirtschaftsstudium zwischen Ideologie und Wissenschaft - Hans Gerhard Strohe (Universität Potsdam, Wirtschafts- und Sozialwissenschaftliche Fakultät, 1996)
– This paper is concerned with the education policy of the GDR state party SED in the field of statistics particularly for students of economics. Statistics was expected to be an instrument of party propaganda. What they called socialist statistics was created on the base of the ideas of Marx, Lenin and Stalin. The personnel policy of the Ministry of Higher Education had to serve these purposes, i.e. only active party members had a chance of getting a professor's job. However, a certain proportion of the academic staff did a good teaching and research work ignoring the official party programmes.
urn:nbn:de:kobv:517-opus-49125
Keywords: 330; Hochschule; Student; Studienrichtung